1989
DOI: 10.1007/bf02389813
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between muscle kinetic parameters and kinematic variables in a complex movement

Abstract: Kinematic variables of the vertical jump (jumping height, jump phase durations and joint angles) were measured on 39 male physical education students. In addition, kinetic parameters of the hip and knee extensors, and of the plantar flexors (maxima voluntary force and its rate of development) were recorded on the same subjects, in isometric conditions. The results demonstrated significant positive correlations between kinetic parameters of the active muscle groups and jumping height (r = 0.217-0.464). The domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
6

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 29 publications
3
30
0
6
Order By: Relevance
“…Regarding the correlations among the CMC variables, the results suggest a moderate relationship between PF and RFD, which is in line with the moderate relationship between Fmax and RFDmax obtained from SST (Jaric et al 1989;Wilson and Murphy 1996;Mirkov et al 2004). This finding should not be considered surprising since the abilities to exert a high maximum force and to exert it rapidly could partly depend on some common factors, such as muscle size, and cross-sectional area and muscle fibre type (Harridge et al 1996;Wilson and Murphy 1996;Mirkov et al 2004).…”
Section: Figuresupporting
confidence: 69%
See 1 more Smart Citation
“…Regarding the correlations among the CMC variables, the results suggest a moderate relationship between PF and RFD, which is in line with the moderate relationship between Fmax and RFDmax obtained from SST (Jaric et al 1989;Wilson and Murphy 1996;Mirkov et al 2004). This finding should not be considered surprising since the abilities to exert a high maximum force and to exert it rapidly could partly depend on some common factors, such as muscle size, and cross-sectional area and muscle fibre type (Harridge et al 1996;Wilson and Murphy 1996;Mirkov et al 2004).…”
Section: Figuresupporting
confidence: 69%
“…This finding has been consistently observed in the literature (Abernethy et al 1995;Driss et al 1998;Kukolj et al 1999;Paasuke et al 2001;Jaric 2002;Jaric et al 2002;Andersen and Aagaard 2006), with relatively few exceptions suggesting only moderate relationships (Jaric et al 1989;Paasuke et al 2001;Wisloff et al 2004). Therefore, there is an apparent need for development of either new or complementary tests for the evaluation of neuromuscular function.…”
Section: Introductionsupporting
confidence: 67%
“…Correlations between voluntary RFD and functional muscle performance has been reported in some studies (Jaric et al 1989;Viitasalo and Aura 1984), whereas others did not establish a relationship (Mero et al 1981;Young and Bilby 1993). These conflicting results may to some extent be related to the time interval in which RFD is determined.…”
Section: Relationship Between Functional Performance and Rfdmentioning
confidence: 75%
“…Young [15] have reported no relationship between maximal isometric force, rate of force development and vertical jumping performance. Similarly, Viitasalo et al [14] have reported no relationship between maximal isometric force and vertical jumping performance, while Jaric et al [6] reported relatively low relationships between maximal isometric force and vertical jumping height. The results of the present study seem to partially support the findings of these previous studies.…”
Section: Discussionmentioning
confidence: 99%